Elevated plasma triglycerides and growth rate are early indicators of reproductive status in post-spawning female steelhead trout (Oncorhynchus mykiss). Issue 1 (26th July 2019) - Jenkins, Laura E; Pierce, Andrew L; Graham, Neil D; Medeiros, Lea R; Hatch, Douglas R; Nagler, James J
Abstract : Activity patterns of desert subterranean tuco-tucos were measured using light-loggers and accelerometers to understand interrelationships among environment, behavior and physiology. Underground temperatures attain minimal values around noon, favoring diurnal time on surface in winter. Timing of highest overall activity shifts to night-time upon transference from field to lab constant conditions. Abstract: Many iteroparous fishes spawn after skipping one or more yearly cycles, which impacts recruitment estimates used for fisheries management and conservation. The physiological mechanisms underlying the development of consecutive and skip spawning life histories in fishes are not well understood. In salmonids, lipid energy reserves and/or growth are thought to regulate the initiation of reproductive maturation during a critical period 1 year prior to spawning. The fasting spawning migration of summer-run steelhead trout ( Oncorhynchus mykiss ) results in significant depletion of energy reserves during the proposed critical period for repeat spawning. To determine whether and when lipid energy reserves and growth influence repeat spawning, measures of lipid energy reserves, growth rate and reproductive development were tracked in female steelhead trout from first to second spawning as a consecutive or skip spawner in captivity. Plasma triglyceride (TG) levels and growth rate were elevated by 10 weeks after spawning in reproductive (i.e. consecutive spawning) versus non-reproductive (i.e. skip spawning) individuals. Muscle lipid (ML) levels, condition factor and plasma estradiol levels increased at later time points. The early differences in plasma TG levels and increases in growth rate are attributable to differential rates of feeding and assimilation between the groups following spawning. A year after spawning, plasma TG levels, MLs and growth rate decreased in consecutive spawners, attributable to transfer of lipid reserves into the ovary. During the year prior to second spawning, energy reserves and plasma estradiol levels were higher in reproductive skip spawners versus consecutive spawners, reflecting the energy deficit after first spawning. These results suggest that the decision to initiate ovarian recrudescence occurs by 10 weeks after first spawning and are consistent with the differences in energy reserves acquired following spawning being a consequence of that decision. This information will increase the success of conservation projects reconditioning post-spawning summer-run steelhead trout.